Teaching Haiti: strategies for creating new narratives - Accilien, Cécile; Orlando, Valérie (University of Florida Press, 2021)
Ayiti se tè glise: Intersectionalities of History, Politics, and Culture / Cécile Accilien and Valérie K. Orlando -- I. Teaching About Haitian Art, Literature, and Language -- Getting Around the Poto Mitan: Reconstructing Haitian Womanhood in the Classroom / Régine Jean-Charles -- Teaching Haiti Through the Work of Rodney Saint-Eloi, écrivain engage / Bonnie Thomas -- Teaching Haitian Theater: Franck Fouch's Bouqui au paradis / Joubert Satyre -- Engaging Haiti Through Art and Religion / Cécile Accilien -- Creating Interdisciplinary Knowledge About Haiti's Creole Language / Don E. Walicek -- II. Teaching About Haitian History and Politics -- Haiti in the Presidencies of John Adams and John Quincy Adams: Lesson Plans and Course Modules / Darren Staloff and Alessandra Benedicty-Kokken -- Teaching the 2004 Coup in Haiti from a French Perspective: Insights into Global Neo-Imperial Culture and Practices / Sophie Watt -- Peck's Fatal Assistance: A Filmic Lesson on the Failures of Aid / Agnès Peysson-Zeiss -- III. Teaching About Haiti in American Studies, Latin American Studies, and General Studies Contexts -- Rendering Haiti Visible in an Introductory American Studies Course / Elizabeth Langley -- Race and Culture on the Thrift Store Shift: Teaching About Haiti Inside and Outside the Academy / Jessica Adams -- Rethinking Latinx Studies from Hispaniola's Borderlands / John Ribó -- Teaching Haiti and the Dominican Republic: Cultural Representations of Haitian Immigrant Experiences / Anne M. François.